Pozioma dywersyfikacja ryzyka z wykorzystaniem analizy sektorowej - Tarczyński, Waldemar; Łuniewska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The idea of using of horizontal risk diversification on the Polish capital market is proposed in the paper. The proposed method is based on the use of information about fundamental power of listed companies. The fundamental power is described by TMAI. The result of the analysis is the creation of three data bases including: all companies, branches and macrobranches. In the next step the portfolios are build from the selected companies from the data bases. All the analyses were done for companies quoted on the Warsaw Stock Exchange in the period of 2002-2005. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 312-319